Biblioteca escolar no processo pré-vestibular:Estudo de caso da Escola Estadual de Ensino Médio Pedro Amazonas Pedroso - CONDER, Taiany Carvalho (2019)
This work presents the Library of the State High School Education Pedro Amazonas Pedroso. Bandeira and Cortê (2011, p.3) address that "the school library needs to be interactive, and constitute a free space for genuine expression of the child, the adolescent and the young." So the problem lies in identifying how the students see the library in the pre-university entrance exam. For this purpose, the context of the library of the State High School Education Pedro Amazonas Pedroso is used as a space for the development of this research, reporting how the students of the third year (senior year) of the morning shift, see and extract information from the information unit. As for the methodological procedures, the exploratory research was used, and to collect the data a bibliographic survey and questionnaires were applied.